Late latent syphilis with early syphilis titer in pregnancy: A case report - Frieda Yanuar; Eka Devinta Novi Diana; Wibisono Nugraha; Ammarilis Murastami; Endra Yustin Ellistasari (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Syphilis is a chronic and systemic sexually transmitted infection caused by Treponema pallidum. The prevalence of syphilis according to the World Health Organization (WHO) is around 12 million cases worldwide and in pregnant women around 1.8 million cases. Syphilis screening in pregnancy is important to break the chain of transmission of congenital syphilis. We reported Mrs. S, 33 years old, 18 weeks pregnant, came with history of itchy patches appeared 8 months ago along with her husband and abortion 1 year ago. The plantar pedis dextra et sinistra showed multiple hyperpigmented macules and no clinical founding in the vagina. Serological tests, reactive Venereal Disease Research Laboratory (VDRL) 1:32, Treponema pallidum hemagglutination (TPHA) >1:5120 and non-reactive human immunodeficiency virus (HIV), support the diagnosis of latent syphilis. Patients were injected with benzathine penicillin 2.4 million units 3 times (1 week apart). Serological test evaluated at months 1, 3 and 6. At month 6, there was a decrease in VDRL value 4 times the initial value, indicating successful therapy in laten syphilis and had received therapy according to the guidelines for late latent syphilis. Syphilis in pregnancy can cause congenital syphilis in the fetus, although latent syphilis has no symptoms. The patient's VDRL titer was reactive in early latent syphilis (>1:8), but based on history and duration of infection more than 1 year including late latent syphilis. Based on this case report, we found that the VDRL titer value did not always correspond to the duration of infection.